THE EDUCATIONAL FUNCTION OF THE FAMILY IN THE PROCESS OF FORMING MORAL ATTITUDES IN CHILDREN - MUNTEANU, Tamara (Acta et Commentationes, Sciences of Education, 2020)
This article represents a theoretical study with practical implications, that elucidate the formation of moral attitudes in children within the family. The article reflects the main characteristics of the family; family functions are listed; parenting styles; the objectives of moral education in the family; the system of parental competences necessary for the efficient achievement of moral education within the family and schematically is reflected the educational function of the family in the process of forming moral attitudes.